2019
DOI: 10.1136/bmjopen-2019-030999
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors forStaphylococcus aureusbacteremia in patients with rheumatoid arthritis and incidence compared with the general population: protocol for a Danish nationwide observational cohort study

Abstract: IntroductionStaphylococcus aureusbacteremia (SAB) is an invasive infection with high mortality and morbidity. Rheumatoid arthritis (RA) is associated with increased risk of infections due to the disease per se and the use of antirheumatic treatments. Few minor studies have previously investigated risk of SAB in patients with RA and indicated increased risk compared with the general population. This nationwide observational study aims to investigate incidence of and risk factors for SAB in adult patients with R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…The exposures of main interest were predefined and included treatment with bDMARDs and glucocorticoids as well as RA disease activity. 24 Users of bDMARDs had received any bDMARD (according to DANBIO) 0-24 months prior to the index date, as opposed to non-users. We subcategorised users according to most recent bDMARD use into either current (0-3 months prior to the index date, 0-12 months for rituximab) or former users (>3 months prior to index date, >12 months for rituximab).…”
Section: Main Exposuresmentioning
confidence: 99%
“…The exposures of main interest were predefined and included treatment with bDMARDs and glucocorticoids as well as RA disease activity. 24 Users of bDMARDs had received any bDMARD (according to DANBIO) 0-24 months prior to the index date, as opposed to non-users. We subcategorised users according to most recent bDMARD use into either current (0-3 months prior to the index date, 0-12 months for rituximab) or former users (>3 months prior to index date, >12 months for rituximab).…”
Section: Main Exposuresmentioning
confidence: 99%
“…The special relationships of the immune system with St. aureus were confirmed by a number of authors. Dieperink et al demonstrated the increased risk of infection due to the RA disease per se regardless of the therapy [61]. The staphylococcal superantigen D gene was found in the synovial fluid and blood of RA patients [62].…”
mentioning
confidence: 99%
“…Beyond articular damage, established RA also substantially increases the risk of systemic complications, such as lymphomas, myocardial infarctions, interstitial fibrosis or susceptibility to infections. Specifically, recent evidence indicates that RA patients display and increased risk of Staphylococcus aureus bacteraemia ( 23 , 24 ). This increased risk may be partially explained by an imbalance in inflammatory pathways during RA pathogenesis, and the use of antirheumatic treatments, that together impair immunity.…”
mentioning
confidence: 99%